Implementasi Filsafat Pendidikan Islam dalam Sistem Terpadu Pembinaan Akhlak dan Tahfizh di PPTQ Ibnu Abbas Klaten - Ariyanto, Ariyanto; Mujiburrohman, Mujiburrohman (TSAQOFAH, 2025)
This study is motivated by the importance of understanding and applying the values of Islamic educational philosophy in shaping students' character and morality, particularly within the context of tahfizh Al-Qur’an education in modern Islamic boarding schools (pesantren). The primary objective of this research is to examine how core values in Islamic educational philosophy are implemented in the development of moral character and the tahfizh process at Pondok Pesantren Tahfidzul Qur’an (PPTQ) Ibnu Abbas Klaten. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and document analysis, including the Director’s Decree, Tahfizh Handbook, and institutional profile. The findings reveal that five principal values, ubudiyah (devotion), khalifah (leadership), ahsan (excellence), adil (justice), and mas’uliyah (responsibility) have been systematically implemented. Ubudiyah is reflected in students’ worship routines and spiritual development; khalifah is evident in the organizational structure and leadership training; ahsan and adil are manifested in a transparent and fair memorization evaluation system; while mas’uliyah is applied through tahfizh quarantine, memorization targets, and active student participation in social and disciplinary activities. The study concludes that the application of Islamic educational philosophy at PPTQ Ibnu Abbas Klaten is comprehensive, integrative, and practical, effectively supporting the holistic goals of Islamic education.